Predictive HR analytics : mastering the HR metric - Edwards, Martin R.; Edwards, Kirsten (London ; New York : Kogan Page Ltd, 2019)
Confidently use predictive analytic and statistical techniques to identify key relationships and trends in HR-related data to aid strategic organizational decision-making.
Chapter - 01: Understanding HR analytics;Chapter - 02: HR information systems and data;Chapter - 03: Analysis strategies;Chapter - 04: Case study 1 - Diversity analytics;Chapter - 05: Case study 2 - Employee attitude surveys - engagement and workforce perceptions;Chapter - 06: Case study 3 - Predicting employee turnover;Chapter - 07: Case study 4 - Predicting employee performance;Chapter - 08: Case study 5 - Recruitment and selection analytics;Chapter - 09: Case study 6 - Monitoring the impact of interventions;Chapter - 10: Business applications - Scenario modelling and business cases;Chapter - 11: More advanced HR analytic techniques;Chapter - 12: Reflection on HR analytics - Usage, ethics and limitations;Chapter - 13: Appendix R
Revised edition of the authors' Predictive HR analytics, 2016.
Includes bibliographical references and index.
CBA
Text in English
Keywords: Personnel management -- Statistical methods